Análisis, diseño e implementación de una aplicación web para el control de mantenimiento y rastreo vehicular del Gobierno Autónomo Descentralizado Municipal de Pasaje mediante tecnología GPS y metodología MSF(Microsoft Solution Framework). - Torres Delgado, Jefferson Santiago (2015)
Currently the use of technology within organizations has now become a necessity because daily they handle large amounts of information which can not be managed and controlled efficiently and effectively through the use of techniques and traditional methods that all they do is delay the process and impatient staff. For this and other reasons the idea of ​​developing a Web Application Control Maintenance and vehicle tracking using GPS technology, relying for analysis, design and implementation of the same methodology MSF is a scalable methodology proposed, designed to expand the scale of the project and adapt to changes that may arise during development, in order to obtain a quality product that helps optimize maintenance activities or operations and vehicle tracking. By implementing the application we were able to automate the following processes: recording information of drivers, vehicles, mechanics, tools and spare parts, administration and planning activities of preventive and corrective maintenance, logistical control of the vehicle fleet by location and design routing, reporting with information on drivers, vehicles and maintenance carried out, among other operations. The application was designed to be accessed from anywhere, therefore was developed for web environment, based on PHP programming language using the CodeIgniter framework that enables rapid development of web applications by minimizing the amount of code needed for a project . The application communicates with an external system to obtain the coordinates emitted by GPS / GSM / GPRS devices located in the vehicles to be displayed on a map using LEAFLET which is a JavaScript library to include interactive maps in a web environment. For storing information manager database like PostgreSQL, which has the ideal characteristics to provide the necessary data to the proper functioning of the application it was used. It previously stated it is concluded that the implementation of the Web Application Control Maintenance and Vehicle Tracking benefit the personnel working in the department called "Automotive Park and Workshops" Autonomous Government Decentralized Municipal Passage, enabling improved performance and performance of the same.